ANALYSIS OF STUDENTS' KINESTHETIC INTELLIGENCE THROUGH EXTRACURRICULAR DANCE ACTIVITIES IN ELEMENTARY SCHOOLS - Putri, Megayanti Hendiana; Sukarno; Daryanto, Joko (Jurnal Dikdas Bantara, 2026)
This research is motivated by the fact that the kinesthetic intelligence of elementary school students through dance extracurricular activities has not been developed optimally, as indicated by the students' difficulties in mastering dance movements. This study aims to (1) analyze the kinesthetic intelligence of students through dance extracurricular activities at Pondok 01 Public Elementary School and (2) describe the supporting and inhibiting factors in the implementation of these activities. This study uses a qualitative approach with research subjects being students in grades I to VI and dance instructors. Data collection was carried out through observation, interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that students' kinesthetic intelligence develops through indicators of body coordination, agility, strength, balance, and visual-motor coordination. Students are able to display more flexible, stable, and synchronous dance movements. Supporting factors include student enthusiasm, teacher and parental support, and opportunities to perform in school and community activities. Inhibiting factors include limited facilities and infrastructure, practice schedules that clash with academic activities, and differences in ability levels among students. Therefore, extracurricular dance activities play a strategic role in developing elementary school students' kinesthetic intelligence if managed optimally.